What do medical specialists think about a proposed academic, integrative health centre in Australia? A qualitative study. (September 2020) - Hunter, Jennifer; Grant, Suzanne; Ee, Carolyn; Templeman, Kate
Highlights: In Australia, integrative healthcare is mostly delivered in the primary care setting. Medical specialists are cautious about traditional, complementary and integrative medicine; particularly safety, opportunity costs and non- evidence-based practice. An academic centre may help mitigate negative attitudes and concerns about integrative healthcare through sound clinical governance and the delivery of high-quality services. Building alliances with the secondary care sector can facilitate bidirectional learning, research collaborations and the centre being recognized as specialists in integrative healthcare. Abstract: Objectives: This qualitative study aimed to explore medical specialists' perspectives on a proposed academic integrative healthcare (IHC) centre to be established in their local district. Methods: A convenience sample of medical specialists were recruited via direct email invitations that was augmented with snowball sampling until data saturation was reached. The in-depth, semi-structured interviews were conducted via telephone, audio recorded and transcribed verbatim, followed by a thematic analysis. Results: Eight participants took part in the study. Three main themes emerged: 1) the benefits of an academic setting, 2) sound clinical governance, and 3) specialists in the field of traditional, complementary and integrative medicine (TCIM). Underpinning the three themes was the belief that patients were at risk of harm due to haphazard, unsupervised use of unproven TCIM. It was anticipated that an academic centre would address these issues with appropriate risk management protocols, effective interprofessional communication, and by upholding the principles of evidence- based practice to ensure safe and coordinated patient-centred care. Opportunities from collaborations within secondary care included centre being recognized as specialists in the field of TCIM, conducting research, and bidirectional learning. Conclusions: The findings demonstrated that medical specialists acknowledged the need for a TCIM model of care that interfaces with the local secondary care landscape through the implementation of sound safeguards, credentialed practitioners, and evidence-based practice to adequately protect patients and clinicians. The findings will be amalgamated with the input from other stakeholder groups via a community-based participatory research framework to refine the model of care.